1957
DOI: 10.1152/ajplegacy.1957.191.2.319
|View full text |Cite
|
Sign up to set email alerts
|

Action of Adrenocorticotropin on Pregnancy and Litter Size in Rats

Abstract: Previously it was reported that adrenocorticotropin (ACTH) displayed the ability to restrict the action of estradiol-17ß in uterine growth and of progesterone in decidual development. This study concerns the influence of a highly purified and potent preparation of ACTH on pregnancy and litter size in albino rats of known reproductive vigor. Experimental procedures consisted of injecting ACTH prior to, immediately after mating and 11 days after mating. These data indicate that ACTH has the ability to reduce lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1964
1964
1996
1996

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Some investigators have suggested that stress-induced increased levels of circulating corticosteroids and/or adrenal androgens would decrease pituitary responsiveness to GnRH, and therefore LH secretion (32)(33)(34)(35)(36), or exert a direct inhibitory action on steroidogenesis (31, 33, 37, 38). Others have reported that ACTH, but not corticosterone, could delay puberty (39), interrupt pregnancy (40)(41)(42), and inhibit ovulation (43). We have recently observed that the intracerebroventricular administration of CRF markedly lowered LH secretion in gonadectomized/ adrenalectomized rats, while acutely large doses of peripherally administered CRF were without effect (13).…”
Section: Discussionmentioning
confidence: 86%
“…Some investigators have suggested that stress-induced increased levels of circulating corticosteroids and/or adrenal androgens would decrease pituitary responsiveness to GnRH, and therefore LH secretion (32)(33)(34)(35)(36), or exert a direct inhibitory action on steroidogenesis (31, 33, 37, 38). Others have reported that ACTH, but not corticosterone, could delay puberty (39), interrupt pregnancy (40)(41)(42), and inhibit ovulation (43). We have recently observed that the intracerebroventricular administration of CRF markedly lowered LH secretion in gonadectomized/ adrenalectomized rats, while acutely large doses of peripherally administered CRF were without effect (13).…”
Section: Discussionmentioning
confidence: 86%
“…Restraint is an effective means of activat¬ ing the hypothalamic-pituitary-adrenal axis (Riegle, 1973) and the specific Stressor used in this study (restraint in a wire-mesh cone) has been shown to raise plasma corticosterone concentrations (and presumably ACTH) 3-fold over those in control mice (Blecha et al, 1982). Both ACTH and adrenal corticoids have been shown to affect pregnant laboratory rodents (Velardo, 1957;Kittinger et al, 1980). Since both hormones show a circadian rhythm in mice and rats (Guillemin, Dear & Liebelt, 1959;Halberg, Peterson & Silber, 1959;Retienne, Zimmermann, Schindler & Lipscomb, 1968) with blood levels peaking before the onset of darkness, it would not be unexpected to see responses to stress varying at different times of the day.…”
Section: Methodsmentioning
confidence: 88%
“…Auditory stimuli at regular intervals for 48 h appeared to interfere with the implantation process in rats (Zondek & Tamari, 1967), but the exact stage of pregnancy at the time of stimulation was not known. Administration of adrenocorticotrophic hormone (ACTH) on the day of mating and for 6 subsequent days reduced the litter size in rats and this effect appeared to be mediated through the adrenal glands (Velardo, 1957). In contrast, Kittinger, Gutierrez-Cernosek, Cernosek & Pasley (1980) reported that ACTH treatment for the first 8 days of pregnancy reduced the number of implantation sites in intact and adrenalectomized mice.…”
Section: Introductionmentioning
confidence: 99%
“…The stress of restraint during early pregnancy decreases the average size of litters in rats (Euker & Riegle, 1973;Herrenkohl, 1979;Wiebold, Stanfield, Becker & Hillers, 1986) and serum progesterone concentrations in mice (Wiebold et al 1986). Involvement of the pituitary-adrenal axis in the maintenance of preg¬ nancy has also been demonstrated in several species (Velardo, 1957;Yang, Yang & Lin, 1969;Christian, 1971;Kittinger, Gutierrez-Cernosek, Cernosek & Pasley, 1980;Rosa & Wagner, 1981;Hellar & de Nicola, 1983). Recently, Kato, Nanjo, Numa et al (1988) demonstrated that adrenocorticotrophin (ACTH) and corticosterone inhibit progesterone secretion during mid-pregnancy in rats.…”
Section: Introductionmentioning
confidence: 99%